Pemaknaan Pinjaman Online Bagi Mahasiswa - Ade Dedi Pamungkas; Fajar Nugraha (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to comprehensively explore the meanings, motives, and experiences of students in using online loan services through a phenomenological approach and a constructivist paradigm. The background of this research is based on the rapid growth of online loan services in Indonesia, which has become increasingly popular among students, especially due to the ease of digital access, fast application processes, and urgent financial needs. This study employs a qualitative method with in-depth interviews conducted with eight active student informants from the Bogor area and its surroundings, all of whom have experience using online loan services.